Implementing Total Quality management practices and Employee Performance: Sanita - Lebanon - Zaiter , Rushdi; Kabbout, Rabih El; Koabaz, Mahnoud; Skaiky, Ahmad; Zalghout, Mohamad; Msheik, Ali (Technium Social Sciences Journal, 2021)
The aim of the study is find out the impact of applying different total quality management (TQM) practices on the performance of employees in the Lebanese industrial sector. The implementation of total quality management in Lebanese companies is very narrow where few companies work to apply Total Quality Management elements and concepts in its operations. Sanita is a Lebanese company that has applied the principles of total quality management relatively in all of its operations, so it has a large share of its products in the Lebanese market. In this quantitative survey designed study, 160 self-administered questionnaires were distributed for employees working at different career level (Top level management / Middle level management / Supervisor / Operator /technician / other workers) in Sanita main branch (Halat -Lebanon) and Sanita factory (Zouk Mosbeh -Lebanon). The survey concluded various questions related to the dependent variable employee performance and the independent variable related to practices of total quality management (leadership, teamwork, training and education, empowerment, communication). Using the quantitative correlation Pearson test, a strong influence emerged for the implementation of TQM principles on the performance of employees at Sanita and its factories; thus accepting the main alternative hypothesis.